Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The mortality and incidence of sequelae of status epilepticus of varying causes was studied in 193 children, ages 1 month to 18 years (mean, 5 years), followed for a mean period of 13.2 months in the Division of Pediatric Neurology, Montefiore Medical Center, 111 E. 210th St, Bronx, NY.